Facing a Pandemic The African Church and the Crisis of AIDS - Bongmba, Elias K. (Waco, Texas Baylor University Press, 2007)
This book debunks the myths about the complicity of the West in inventing HIV/AIDS. Bonggmba refocuses our attention on the grim and irrefutable data about the toll that many of the unwise and corrupt policies of African governments have taken on the li
Keywords: AIDS (Disease) -- Africa. HIV infections -- Africa. AIDS (Disease) -- Religious aspects -- Christianity